EVALUASI KEPUASAN MASYARAKAT TERHADAP KUALITAS INFRASTRUKTUR KOTA BALIKPAPAN DENGAN METODE CUSTOMER SATISFACTION INDEX (CSI) - Dewi, Dhyah Puspita; Wibisono, Priyo; Tufail, Dwiana Novianti (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
The city of Balikpapan, as one of the main economic centers in Kalimantan, faces significant challenges in providing adequate urban infrastructure. Most previous evaluations have focused on physical aspects, whereas public satisfaction as direct users provides a more concrete measure of development outcomes. This study aims to evaluate the quality of urban infrastructure in Balikpapan using the Customer Satisfaction Index (CSI) approach. A quantitative method was applied through a Likert-scale questionnaire distributed to residents across six districts. The results show that the overall CSI value for Balikpapan falls within the “moderately satisfied” category. At the district level, the highest score was recorded in Balikpapan Kota District (73%), while the lowest was in Balikpapan Barat District (59%). At the sub-district (kelurahan) level, Gunungsamarinda Baru achieved the highest CSI score at 77%, whereas Kariangau recorded the lowest at 47%. These findings indicate variations in public satisfaction levels across different areas and highlight the need for more targeted policy interventions in regions with lower satisfaction scores. This study concludes that measuring public satisfaction using CSI is essential, particularly as a basis for developing more responsive and equitable urban infrastructure policies.